1993
DOI: 10.1128/aac.37.4.685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on anti-Candida activities of antifungal antibiotics

Abstract: The relative growth (percentage of growth relative to control growth) of 767 Candida isolates representing five species was measured in microcultures at 25 and 37°C. In the presence of 10-4 M flucytosine, the distribution of relative yeast growth data indicated that Candida albicans isolates were less susceptible at 25°C than at 37°C, while the opposite was found with 4 x 10-s M amorolfine for most of the isolates tested.Repetition of the experiments at four different temperatures with 99 C. albicans isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…(107 C. albicans isolates, 41 C. glabrata isolates, 16 C. krusei isolates, 17 C. tropicalis isolates, and 16 isolates representing 7 other species). The arithmetic mean OD (SD) was 1.037 (0.160), the geometric mean was 1.020, the lowest reading was 0.257, and the highest reading was 1.445; these measurements generally matched previously published results (18 By contrast, the flucytosine susceptibility test outcome varied considerably with the initial yeast concentration. At least 10 of the 29 isolates tested showed inoculum size-dependent variations in ICs that exceeded 2 dilution steps.…”
Section: Selection Of Well Cross-section and Spectrophotometric Readisupporting
confidence: 75%
“…(107 C. albicans isolates, 41 C. glabrata isolates, 16 C. krusei isolates, 17 C. tropicalis isolates, and 16 isolates representing 7 other species). The arithmetic mean OD (SD) was 1.037 (0.160), the geometric mean was 1.020, the lowest reading was 0.257, and the highest reading was 1.445; these measurements generally matched previously published results (18 By contrast, the flucytosine susceptibility test outcome varied considerably with the initial yeast concentration. At least 10 of the 29 isolates tested showed inoculum size-dependent variations in ICs that exceeded 2 dilution steps.…”
Section: Selection Of Well Cross-section and Spectrophotometric Readisupporting
confidence: 75%
“…7 While the majority of clinical terbinafi ne use is observed with infections caused by dermatophytes, the susceptibility of numerous organisms including pathogenic yeast, dematiaceae, thermally dimorphic fungi and hyaline hyphomycetes has been evaluated. [8][9][10][11][12][13][14][15][16] Although the nature of the assays employed precludes direct comparison of minimum inhibitory concentrations (MICs) between studies (ie, some were performed prior to standardization of a reference method by the Clinical and Laboratory Standards Institute (CLSI), 17 some universal trends are repeated throughout. Namely, terbinafi ne demonstrates the greatest activity against species within the Trichophyton, Microsporum, and Epidermophyton genera followed by the dematiaceae, the fi lamentous fungi and a few selected pathogenic yeast.…”
Section: Clinical Mycologymentioning
confidence: 99%
“…We found that these two fungal pathogens exhibited increased susceptibility to KC at 37°C compared to 30°C. The temperature-related sensitivity to antimicrobial therapy has been reported previously (65,66).…”
Section: Discussionmentioning
confidence: 94%